Pengaruh Sosial Ekonomi terhadap Minat Pemuda dalam Berwirausaha Ayam Potong di Kota Palopo - Andi Rizkiyah Hasbi; Sari Ratna Dewi (Fakultas Pertanian, Universitas Timor, 2022)
In taking business and market prospects, Socioeconomic factors may become worse as a result of the increasing level of competition between abattoir entrepreneurs. This study aims to determine what characteristics influence the youth's interest in broiler chickens entrepreneurship in Palopo City. The technique used in this sampling is incidental sampling, which is the technique of determining the sample based on the coincidence with a total sample of 33 people. The analytical tool used is Multiple Linear Regression which is used to determine and predict the socio-economic influence (income, family environment, and social status) on youth interest in chicken entrepreneurship. Based on the results of the study, the F-count value for the variables of income, family environment, and social status simultaneously on youth interest is 452,916 > F-table value is 2.89 and a significance of 0.000 <0.05, it can be concluded that income, family environment, and social status simultaneously has a significant effect on youth interest in beef chicken entrepreneurship. Based on the T-test, income has a partial effect on the youth's enthusiasm for entrepreneurship in beef chicken, for the family environment variable does not affect the youth's interest in entrepreneurship in beef chicken. And for the social status variable, it is stated that social status does not affect youth's interest in beef chicken entrepreneurship.